2021
DOI: 10.1097/nmd.0000000000001429
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Care Unit in Children and Adolescents With Autism Spectrum Disorder

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder that affects social interactions and behavior. The number of children and adolescents with ASD treated in mental health services has been growing in recent years. Knowing clinical and familial characteristics of hospitalized patients with ASD and multidisciplinary approach are crucial for children and adolescents mental health professionals. In this study, 253 Turkish children and adolescents, with and without ASD, treated in psychiatry in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In our study, about 80% of the patients with ASD were males, which is in line with previous studies. Ozbaran et al (2022) found that there were more male inpatients with ASD than female ones. Other previous studies showed that male sex dominance is seen in hospitalized ASD patients (Kuriakose et al, 2018; Taylor et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, about 80% of the patients with ASD were males, which is in line with previous studies. Ozbaran et al (2022) found that there were more male inpatients with ASD than female ones. Other previous studies showed that male sex dominance is seen in hospitalized ASD patients (Kuriakose et al, 2018; Taylor et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, in our study, the rates of major depressive episodes and suicidal thoughts at admission were found to be notably lower in the ASD group than in the non-ASD group. In a study conducted by Ozbaran et al (2022), the rate of suicide attempts was also found to be significantly lower in the ASD group. These findings may be relevant to hospitalized patients with ASD but not to the general population of individuals with ASD and no ID (Newell et al, 2023).…”
Section: Comparison Of Individuals With Asd Versus Individuals With N...mentioning
confidence: 90%
See 2 more Smart Citations